Kin-based alloparenting and infant hospital admissions in the UK Millennium cohort. Issue 1 (18th June 2020) - Waynforth, David
Abstract: Background and objectives: Kin-selected altruism is an evolutionary explanation for why biological kin other than parents are willing childcare providers or alloparents. Kin alloparents may increase lineage fitness by reducing maternal energy depletion and improving child survival through childcare activities. The aim of this research was to apply the hypothesis that kin-based alloparental care has benefits for child health in a western, educated, industrialized, rich, democratic context. Methodology: The hypothesis was tested using the first sweep of the UK Millennium Cohort Study ( n = 18 552 infants). The outcome was number of hospitalizations by age 9 months, and the main predictors were kin-based alloparental care during work hours, socioeconomic position and infant health-related variables and their interactions with kin-based alloparenting. Analysis of hospitalizations was carried out using negative binomial regression. Results: Kin alloparents were primary day carers in 17% of households. Infants whose main care arrangement during work hours was with kin allocarers had statistically significantly fewer hospitalizations than infants in all other care arrangements combined (Incidence rate ratio = 0.86, P < 0.03), and when contrasted with maternal day care (Incidence rate ratio = 0.79, P < 0.02). Conclusions and implications: Kin-based allocare was associated with about a 15% reduction in the risk of infant hospitalization in the first 9 months. The difference appeared to be due in part to a difference in the risk of hospitalization for infectious diseases. Sensitivity analyses indicated that infants cared for by their mother during the day rather than in day-care facilities were most at risk of hospitalization compared with those in kin-based care. Lay summary: Modern industrialized societies are generally characterized by nuclear family households, with grandparents and other extended family often living a considerable distance away. Studies carried out in societies which have not undergone the fragmentation of extended families have shown that grandmothers and other biological kin reduce infant mortality, most likely because they distribute the burden of infant care so that it does not fall exclusively on the mother. Here, the hypothesis that grandparental and other family care would be beneficial for infant health in the contemporary UK was testing using the UK Millennium cohort. Infant health was measured as number of hospitalizations in the first 9 months from birth. The main findings were that kin-based infant care, which was most commonly by grandparents, was associated with a 15% reduction in the risk of hospitalization in infants up to 9 months of age. Further analysis suggested that the difference was larger for risk of infant hospitalization due to infectious diseases rather than non-infectious diseases. The results also suggested that the finding may have been driven by increased risk for infants of mothers caring for their infant during normal working hours with no other help, such as from the father or pay-for day-care.